EU public aid and risk management in agriculture − selected legal aspects - Lipińska, Izabela (Przegląd Prawa Rolnego, 2018)
The aim of the deliberations was to determine the scope and principles of granting public aid to support risk management in agriculture. The normative solutions contained in primary and secondary EU law have been analysed. It has been concluded that the specificity of agriculture and the accompanying risk require public support. The granting of aid should be properly shaped and stimulated. This is because of its universality and easy accessibility, which may reduce farmers’ efforts to take independent remedial measures when selecting legal risk management instruments. From an economic point of view, the granting of this aid leads to a change in the relationship between the equity and other production factors in agriculture.